Informing Pedagogical Action: Aligning Learning Analytics With Learning Design. (October 2013) - Lockyer, Lori; Heathcote, Elizabeth; Dawson, Shane
This article considers the developing field of learning analytics and argues that to move from small-scale practice to broad scale applicability, there is a need to establish a contextual framework that helps teachers interpret the information that analytics provides. The article presents learning design as a form of documentation of pedagogical intent that can provide the context for making sense of diverse sets of analytic data. We investigate one example of learning design to explore how broad categories of analytics—which we call checkpoint and process analytics —can inform the interpretation of outcomes from a learning design and facilitate pedagogical action.